ACTUALIZATION AND ACTUAL DIVISION IN POETIC SPEECH (Scientific journal of the Fergana State University, 2024)
This article examines the compositional and syntactic structure of poetic speech, which is considered one of the problematic issues in the field of poetic syntax, and theoretical views on the study of division itself in it. The communicative approach to speech analysis determines the position of the author of the speech as an addressee, the ability to use speech capabilities and means, his attitude to the reality being described, methods and means of transmitting information about the information being transmitted. information or subject-event and its features, speech composition - is considered important in syntactic construction, another form of semantic-syntactic relations between parts of poetic speech manifests itself in the form of actual division and plays an important role in compositional construction. syntactic formation of speech, the relationship between theme and rheme in syntactic units - a semantic category of linguistics that forms the problem of the actual division of a sentence, the expressive basis of a sentence - the theme and the core of the expression - the rheme are determined, according to most scientists, by units of actual division, in the syntactic construction, the author of the speech and the listener or readers are part of the communication mechanism. topic - if the topic is known to both of them in advance, rhema is a new message, information transmitted by the addressee. It is important to study it as a separate category when studying Uzbek poetic speech within the framework of Uzbek poetics. All these categories are explained based on the experience of world linguistics.